The Influence of Images of Climate Change Causes, Consequences, and Solutions on the Relationships Between Pro-Environmental Motivation and Change in the Intentions to Engage in Pro-Environmental Behaviors: A Comparison of Motivational Frameworks - Dorville, Maxime (Université d'Ottawa / University of Ottawa, 2020)
Some human actions are linked to the decline of the environment on a planetary scale. In order to motivate individuals to adopt pro-environmental behaviors (PEBs), it is important to understand how individuals react when exposed to persuasive messages. The goal of this program of research was to examine the influence of images of climate change causes, consequences, and solutions on the relationships between environmental motivation, psychological discomfort, discomfort compensation strategies, as well as changes in pro-environmental attitude and PEBs. In Study 1 (N = 199), I identified visual stimuli (pictures) depicting causes, consequences or solutions to global warming to be used in Study 2. Also, I examined the relationship between environmental motivation and competency on the perception of these pictures. The results indicated that the pictures depicting causes or consequences were perceived more negatively than pictures depicting solutions. In addition, findings showed that regardless of the individual’s perceived level of environmental competence and their type of motivation towards PEBs, individuals had a negative perception of pictures depicting causes and consequences to global warming as well as a positive perception of pictures related to solutions to global warming. In Study 2 (N = 312), I examined the relationships between environmental motivation, psychological discomfort, discomfort compensation strategies, as well as changes in pro-environmental attitude and PEBs following the exposition to images identified in Study 1. Three models based on Self-Determination Theory (SDT), Action-Based Model, and the Hierarchical Action-Based model of Inconsistency Compensation in the Environment (HABICE) domain were examined. The results indicated that exposure to pictures alone is not enough to generate a significant change in pro-environmental attitude or PEBs. The findings showed that the SDT model was best suited to explain the process leading to PEBs changes when exposed to pictures depicting causes of global warming. Finally, the results indicated that the HABICE model was best suited to explain changes in pro-environmental attitude when individuals are exposed to pictures depicting consequences. The HABICE was also a good model to explain the relationships among the different variables when individuals are exposed to pictures depicting solutions to global warming. Overall, this program of research contributed to both SDT and the HABICE models by supporting their conceptual framework.
Keywords: Self-Determination Theory; Pro-Environmental Behaviors; Environmental Motivation; Environmental Messages; HABICE Model; Cognitive Dissonance